GLOBALISASI MIGRASI DAN PERAN DIASPORA: Suatu Kajian Pustaka - Haning Romdiati (Research Centre for Population, Indonesian Institute of Sciences, 2015)
This paper aims to understand how is the globalization of migration and the role of the diaspora to their country of origin. Though it has remained largely untested, it is commonly assumed that international migration has accelerated as part of globalization processes. The broad trend of the globalization of migration assumes to be one of contributing factor to establishment and engagement of diaspora. Globalization of Migration measured by an increase in stock and widening in geographical scope of international migration may occur mainly due revolution of information, communication, and transportation that have significantly reduced the cost of migration. Such situation not only increases in the volume of migration but also generates the shift in global migration pattern. The change to new destination followed by the rise of migration are more likely to connect immigrants into one big community or to join to existing diaspora to ensure their transnational life and also to keep well and strong connection with their homeland. Diaspora that has been long established affects development in countries of origin. Such participation in development is not only in remittances, but also in building bridges between countries of origin and destination which convey in economic activity, transfers of, skills, technological development, and cultural enrichment.